2016
DOI: 10.22267/rus.161801.24
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional y determinantes sociales en niños entre 0 y 5 años de la comunidad de Yunguillo y de Red Unidos, Mocoa - Colombia

Abstract: Estado nutricional y determinantes sociales en niños entre 0 y 5 años de la comunidad de Yunguillo y de Red Unidos, Mocoa -ColombiaNutritional status and social determinants in children between 0 and 5 years old from the community of Yunguillo and "Red Unidos" in Mocoa, Colombia ResumenObjetivo: Establecer el estado nutricional de los niños de 0 a 5 años de la comunidad del Resguardo Yunguillo y de Red Unidos del municipio de Mocoa 2014 y su relación con los determinantes sociales. Materiales y métodos: Estud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
2
Order By: Relevance
“…Arias et al studied the case of the Arhuaco indigenous group, and again, the results showed high rates of malnutrition and stunting compared to the national averages and to other indigenous groups in Latin America [46]. Vallejo-Solarte et al, on the other hand, showed malnutrition and stunting in approximately 50% of the children from 0 to 5 years of age in the community of the Yunguillo Reservation in the municipality of Mocoa, Putumayo [47]. These results reflect the nutritional vulnerability of the indigenous population in Colombia and the lack of progress over time.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Arias et al studied the case of the Arhuaco indigenous group, and again, the results showed high rates of malnutrition and stunting compared to the national averages and to other indigenous groups in Latin America [46]. Vallejo-Solarte et al, on the other hand, showed malnutrition and stunting in approximately 50% of the children from 0 to 5 years of age in the community of the Yunguillo Reservation in the municipality of Mocoa, Putumayo [47]. These results reflect the nutritional vulnerability of the indigenous population in Colombia and the lack of progress over time.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Investigaciones previas revelan la dificultad que presentan estas poblaciones frente al acceso a sistemas de educación y salud, lo que provoca condiciones adversas para la integración social (Bustillo, 2004;Machado Duque, Calderón Flórez y Machado Alba, 2014;Silva y Guataquí, 2011;UARIV, 2014;Vallejo, 2007;Vallejo Solarte, Castro Castro y Cerezo Correa, 2015). La participación laboral de personas en edad escolar afecta los rendimientos futuros no solo individuales, sino de la familia en su conjunto.…”
Section: Desplazamiento Forzado De Poblaciones Indígenas Y Afrodescendientes: El Caso Colombianounclassified
“…Malnutrition is closely linked to poverty [ 1 ] and within health inequities, stunting responds to environmental and socioeconomic determinants [ [7] , [8] , [9] , [10] , [11] , [12] ], such as maternal education, home hygiene [ 13 ], age and sex of the child, period between births, age of the mother at the birth [ 14 ], the low birth weight and poor health of the pregnant [ 15 ]; therefore, in rural conditions, considering that the impact variable of the nutritional food system is stunting, this indicator must be correctly evaluated [ 16 ].…”
Section: Introductionmentioning
confidence: 99%